2011
DOI: 10.3109/s10165-011-0432-9
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of total joint arthroplasty in patients with established rheumatoid arthritis: improved longitudinal effects on disease activity but not on health-related quality of life

Abstract: Though excellent clinical results have been reported for total joint arthroplasty (TJA) in rheumatoid arthritis (RA) patients, the longitudinal effects of TJA on pain, physical function, and health-related quality of life in RA patients remain unknown. This study aimed to assess changes in disease activity and health-related quality of life after TJA in patients with established RA. We analyzed the effect of total knee arthroplasty (TKA) and total hip arthroplasty (THA) on RA disease activity in an observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…Thus, there seems to be a relationship between the intensity of inflammation and the patient's satisfaction with a pain‐free condition at the site of surgery. Some previous reports demonstrated that surgical intervention, especially synovectomy and arthroplasty, enhances the amelioration of systemic disease activity as well as joint function . In this study, the elbow, wrist and hand surgeries might have enhanced the amelioration of the disease activity to some extent.…”
Section: Discussionsupporting
confidence: 49%
“…Thus, there seems to be a relationship between the intensity of inflammation and the patient's satisfaction with a pain‐free condition at the site of surgery. Some previous reports demonstrated that surgical intervention, especially synovectomy and arthroplasty, enhances the amelioration of systemic disease activity as well as joint function . In this study, the elbow, wrist and hand surgeries might have enhanced the amelioration of the disease activity to some extent.…”
Section: Discussionsupporting
confidence: 49%
“…Total arthroplasty is also expected to restore ADL. Momohara et al . reported that although DAS28 had improved 5 years after TKA or total hip arthroplasty (THA), Japanese‐HAQ(J‐HAQ) remained unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…At baseline (just before TKA) and 12 weeks after TKA, CRP, ESR and matrix metalloproteinase‐3 (MMP‐3) were measured as inflammation and cartilage markers. The Disease Activity Score of 28 joints (DAS28)‐ESR and DAS28‐CRP, clinical disease activity index (CDAI) and simplified disease activity index (SDAI) were used to evaluate RA disease activity. TJC and SJC for the above‐mentioned 28 joints, PVAS and EVAS were also assessed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…THA and TKA may possibly have additional effects on RA disease activity. Previously, it was reported that disease activity after THA and TKA, as evaluated by the DAS28, had decreased in patients with RA [19]. Inflamed knee joints greatly affect RA disease activity, and are readily identified because the knee joint is included in the DAS28, SDAI and CDAI assessments.…”
Section: Discussionmentioning
confidence: 99%